Avaliação da resposta pulpar humana diante de diferentes técnicas de clareamento - Vaz, Maysa Magalhães (2015)
Tooth bleaching is the first alternative for obtaining a harmonious smile. However, the bleaching material can cause damage to the pulp. This study aimed to characterize the human pulp response before different bleaching techniques. Twenty-nine volunteers (n = 29) were included in the study and divided into 3 groups. The human third molars with extraction indication of these patients were used. The groups were divided according to the bleaching technique performed: control group - was not performed any bleaching technique (n = 7); Group 01- home bleaching with carbamide peroxide 15% (n = 10); Group 02- professional whitening with hydrogen peroxide 38% (n = 12). The teeth were extracted and the pulp removed and stained with hematoxylin and eosin (H & E) or subjected to immunohistochemistry for microscopic evaluation of immunostained cells and analysis. In microscopic analysis, the groups were evaluated for intensity of the inflammatory infiltrate, collagen degradation and organization of the pulp tissue. For immunohistochemicaltechnique have been identified: mast cells (tryptase positive), macrophages (CD68 +) and blood vessels (CD 31+). Data were submitted to descriptive analysis and, as a result, processed by the statistical program (Chi Square to the criteria evaluated the technique of H & E and Kruskal-Wallis followed by Mann Whitney for the data of immunohistochemistry: values less than 0, 05 were considered statistically significant). The microscopic analysis, groups showed statistically significant differences for the intensity criterion of the inflammatory infiltrate (p <0.05) but not for collagen degradation (p> 0.05) and organization of the pulp tissue (p> 0.05). The findings of immunohistochemistry showed statistical difference between the density of macrophages, being higher in Group 2. When compared in pairs, there was the Group 2 for the remaining difference (p <0.05) but not between Groups Control and domesticated (p> 0.05). The blood vessels presented with similar density among the three groups (p> 0.05) and were not found mast cells. It was concluded that the professional whitening results in a more intense inflammatory response and increased pulp damage when compared to home bleaching in molars.